2012
DOI: 10.1111/j.1432-2277.2012.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for hepatocellular cancer: UCL experience in 137 adult cirrhotic patients. Alpha-foetoprotein level and locoregional treatment as refined selection criteria

Abstract: Summary Liver transplantation (LT) is a validated treatment for selected cirrhotics with hepatocellular cancer (HCC). A retrospective single center study including 137 recipients having proven HCC was done to refine inclusion criteria for LT as well as to look at impact of locoregional treatment (LRT) on outcome. At pre‐LT imaging, 42 (30.6%) patients were Milan criteria (MC)‐OUT; 28 (20.4%) were University of California San Francisco criteria (UCSFC)‐OUT. Pre‐LT LRT was performed in 109 (79.6%) patients. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 39 publications
1
38
0
2
Order By: Relevance
“…The most frequent cutoff value reported in the literature is 400 ng/mL. This has been reported by authors from various countries in Asia [63] , Europe [64,65] and the United States [49,59,66] . It appears to be linked to recurrence but also to the risk of dropout while on a waiting list.…”
Section: Defining a Cut-off Value For Afpmentioning
confidence: 79%
“…The most frequent cutoff value reported in the literature is 400 ng/mL. This has been reported by authors from various countries in Asia [63] , Europe [64,65] and the United States [49,59,66] . It appears to be linked to recurrence but also to the risk of dropout while on a waiting list.…”
Section: Defining a Cut-off Value For Afpmentioning
confidence: 79%
“…Hepatosellüler kanserin tedavisi için yapılan karaciğer nakli sonrası görülen kanser nüksleri, bu tedavi yönteminin en kaygı verici sonuçlarından biridir (14). Bizim çalışmamızda görülen %14.7 oranındaki nüks ve nüks gelişen hastalardaki düşük sağkalım oranlarının literatürde yayınlanan önceki çalışmalarla uyumlu olduğu görüldü (3,6,15).…”
Section: Discussionunclassified
“…Çünkü bu kriterler dışında, tümörün diğer özelliklerinin de nüks ve sağkalım üzerine olan etkisi daha önce yapılan birçok çalışmada ortaya konulmuştur (14,18). Çalışmamızda da bu sonuçlara paralel olarak kanser nüksünü arttıran faktörler arasında; tümörün çapı, multifokal ve kötü diferansasyon göstermesinin önemli olduğu görüldü.…”
Section: Discussionunclassified
“…An Italian study showed that the combination of morphological and biological parameters (e.g., total tumor diameter > 8 cm and AFP > 400 ng/mL) conferred scarce survivals: patients having the last AFP value > 400 ng/mL had an eighttimes incremented risk of tumor recurrence after transplantation [9] . A monocentric Belgian study similarly identified the last AFP determination > 400 ng/mL as the most important independent predictor for tumor recurrence after LT (HR = 4.86; P = 0.01) [10] . The United Network for Organ Sharing region 6 experience showed that peak AFP value > 400 and AFP at LT > 400 ng/mL were connected with poor outcomes post-LT in patients previously treated with loco-regional treatment (LRT) [11] .…”
Section: Recurrence: Role Of Static Valuesmentioning
confidence: 97%
“…195 China 400 Lai et al [9] 2012 158 Italy 400 Ciccarelli et al [10] 2012 137 Belgium 400 Wong et al [11] 2013 211 United States 400 Yang et al [17] 2007 63 (LDLT) South Korea 1000 Zou et al [18] 2008 303 China 1000 Duvoux et al [19] 2012 435 France 1000 Hameed et al [20] 2014 211 United States 1000…”
Section: From Static To Dynamicmentioning
confidence: 99%